Bibliometric Analysis of Two Decades of Global Research on the Ethnopharmacological Value of Pimpinella pruatjan - Mohamad Kashuri (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2026)
Research on Pimpinella pruatjan (Apiaceae, locally known as purwoceng), an Indonesian medicinal plant valued for its aphrodisiac properties and cultural significance, remains limited in terms of global visibility and scientific recognition. To address this gap, a bibliometric assessment spanning two decades (2005–2025) was conducted using the Scopus database and a PRISMA-based screening approach, with VOSviewer applied to map publication trends, collaboration networks, institutional productivity, and thematic density using Callon centrality profiling. Findings reveal a fragmented yet progressively growing research landscape, dominated by non-endemic countries such as Iran and Japan, whereas contributions from Indonesia remain limited. Existing studies predominantly focus on reproductive pharmacology and phytochemical characterisation, while toxicological validation, clinical testing, and ecological sustainability remain largely underexplored. Thematic mapping also exposes weak research collaboration, methodological inconsistency, and limited engagement with indigenous knowledge holders. Advancing P. pruatjan as a credible phytomedicine necessitates standardised cultivation practices, comprehensive toxicological and clinical investigations, and inclusive international collaborations that strengthen local institutional capacity. Strengthening interdisciplinary collaboration and institutional commitment will enhance Indonesia’s role in global ethnopharmacology and promote sustainable innovation in evidence-based herbal medicine.